Barriers to the utilization of research and implementation of evidence-based practice among nurses in Sabah, Malaysia: Across-sectional study - Nadirah Sulaiman; Seah, Peter Keng Tok; Juhanah Gimbo; Ammar Rafidah Saptu; Phylis Bridget Philip; Yau Kim Yain; Lilyiana Pengui; Drina Dalie (MDPI, 2025)
Evidence-based practice (EBP) has been widely adopted in clinical nursing practice, with nursing education efforts consistently emphasizing its importance in strengthening implementation efforts. Despite these efforts to promote translational research, the level of implementation of evidence-based practice (EBP) in clinical nursing practice remains unsatisfactory. This study aimed to identify specific organizational, individual, and research-related barriers to the utilization of research in clinical practice among nurses in Sabah, Malaysia, to determine factors associated with these perceived barriers and to assess nurses’ awareness and understanding of the implementation of evidence-based practice. A cross-sectional study was conducted in 2019 using the BARRIERS scale, a validated tool that measures perceived barriers to the utilization of research across four domains: organizational barriers, nurses’ research awareness and values, quality of research, and research communication. This study involved nurses from five tertiary hospitals in Sabah, Malaysia. A total of 562 nurses participated in the study, with a mean age of 34.3 years (SD = 7.96) and mean duration of clinical practice of 10.0 years (SD = 7.58). While 66.5% of the nurses had heard of EBP, only 7.3% reported understanding it very well. The top three barriers to the utilization of research were ‘the nurse does not feel she/he has enough authority to change patient care procedures’ (35.9%), ‘the nurse does not have time to read research’ (27.8%), and ‘research reports/articles are not published fast enough’ (25.8%). Among the four domains, organizational barriers scored highest (mean = 2.7, SD = 0.72), followed by research communication (mean = 2.6, SD = 0.73). Conclusions: The study findings emphasize the challenges nurses encounter in integrating research into clinical practice and highlight the need for ongoing efforts to promote the utilization of evidence-based practice and research among nurses in Sabah, while addressing the identified gaps.